The Effect of Carnosol, Carnosic Acid and Rosmarinic Acid on the Oxidative Stability of Fat-Filled Milk Powders throughout Accelerated Oxidation Storage - Katerina Tzima; Nigel P. Brunton; Noel A. McCarthy; Kieran N. Kilcawley; David T. Mannion; Dilip K. Rai (MDPI AG, 2021)
The in vitro antioxidant effects of the most potent antioxidants of rosemary, namely carnosol, carnosic acid and rosmarinic acid (c: ca: ra) were assessed in fat-filled milk powders (FFMPs) under accelerated conditions (40 °C and relative humidity (RH) 23%) over 90 days. Lipid oxidation was assessed in FFMPs by measuring peroxide values (PVs), thiobarbituric acid reactive substances (TBARS) and aroma volatiles using headspace (HS) solid-phase microextraction (SPME) coupled to gas-chromatography-mass spectrometry (GC-MS). The antioxidant potency of c: ca: ra exhibited a concentration-related effect (308 ppm > 200 ppm > 77 ppm), with the highest concentration being the most effective at controlling the formation of TBARS and PVs. At a concentration of 308 ppm c: ca: ra were particularly effective (p < 0.05) in inhibiting all the evaluated oxidation indices (primary and secondary) compared to the control samples, but in some cases less effectively (p < 0.05) than butylated hydroxyanisole: butylated hydroxytoluene (BHA: BHT) (200 ppm).